Comparative evaluation of three PCR base diagnostic assays for the detection of pathogenic trypanosomes in cattle blood - Thumbi, Samuel M.; McOdimba, F.A.; Mosi, R.O.; Jung'a, J.O. (Springer, 2008)
Currently, several PCR based diagnostic assays have been developed to improve the detection of pathogenic trypanosomes. These tests include use of species specific primers, single and nested PCRs' based on primers amplifying the Internal Transcribed Spacer (ITS) regions of ribosomal DNA. This study compares three PCR based diagnostic assays and assesses the agreement of these three asaays by screening 103 cattle blood samples randomly collected from trypanosome endemic areas in western Kenya. The nested ITS based PCR, the single ITS based PCR and the species specific based PCR detected 28.1%, 26.2% and 10.7% of the samples respectively as positive for trypanosome infection. Nested ITS and single ITS PCRs' picked 3.8% and 1.9% as mixed infections respectively. Cohen kappa statistic used to compare agreements beyond chance between the assays showed highest degree of agreement (0.6) between the two ITS based tests, and the lowest (0.2) between the nested PCR test and the species specific PCR. The single ITS and nested ITS based diagnostic assays detected higher numbers of positive cases, and reduced the number of PCR reactions per sample to one and two respectively, compared to the five PCR reactions carried out using the species specific primers. This significantly reduced the labour, time and the cost of carrying out PCR tests, indicating the superiority of the ITS multi-species detection techniques. Reliable epidemiological studies are a prerequisite to designing effective tsetse and trypanosomiasis control programs. The present study established the suitability of using ITS based PCR assays for large-scale epidemiological studies.